A RESEARCH STUDY OF METHODOLOGY OF IMAM IBN E ABI HATIM IN HIS BOOK “AL-ILAL” - Dr. Hafiz Muhammad Sani; Bakht Shaid (jihat-ul-islam, 2021)
Imam Abdur Rahman Ibn e Abi Hatim was a great Muhadith. He was born in 240A.H. He got the knowledge of Quran and Sunnah from his father Imam Abu Hatim al-Razi and Imam Abu Dhura al-Razi. He wrote a book about the naratios which name is “Al-Jarh wa Al-Tadil”. This book is an original and basic source about the naratios. He also wrote a book about Marasil in which he explained this kind of Ahadith. He wrote another book named “Al-Ilal” which discussed an important and difficult side of Uloom e Hadith. In this book he explained the Ilal of Ahadith. He wrote the openions of his father and Imam Abu Dhura and explained some Ahadith by himself. Imam Ibe Abi Hatim wrote the book like books of Fiqh. He started his book from Taharth and in the end of the book is Ijarat.